2019
DOI: 10.22207/jpam.13.4.41
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Mycoplasma from Starlings Lungs

Abstract: Starlings have tremendous economic and environmental impacts because they can spread pathogensto livestock and poultry. These birds act as mechanical and biological carriers for different types of pathogens from and to their original habitat. The goal of this study was to ascertain the presence of Mycoplasma gallisepticum (MG) in the starlings' lungs and confirm their diagnosis using the PCR technique. We altered the supplements that were added to Mycoplasma culture media by using calf serum instead of horse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For the diagnoses of MG by PCR technique, two pairs of PCR primers were used Table 1 and consisted of universal primer pair for the genus of Mycoplasma depending on 16S rRNA sequences and the second pair was specific for MG according to ( Aghabalaei and Hedaiati, 2012 ; Malekhoseini et al ., 2017 ), and the efficacy of these primers was confirmed by ( Hamad et al ., 2019a , 2019b ; Al-dabbagh et al ., 2021 ). primers were synthesized by Bioneer Co., Korea.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…For the diagnoses of MG by PCR technique, two pairs of PCR primers were used Table 1 and consisted of universal primer pair for the genus of Mycoplasma depending on 16S rRNA sequences and the second pair was specific for MG according to ( Aghabalaei and Hedaiati, 2012 ; Malekhoseini et al ., 2017 ), and the efficacy of these primers was confirmed by ( Hamad et al ., 2019a , 2019b ; Al-dabbagh et al ., 2021 ). primers were synthesized by Bioneer Co., Korea.…”
Section: Methodsmentioning
confidence: 71%
“…PCR reaction was operated in whole size 25 µl as in Kit and consisted of: 5 µl from extracting DNA (template), 1 µl of every primer, 2 µl of MgCl 2 , 6 µl of PCR water, and 10 µl of 2.5× prepared Mastermix solution. The control positive in both PCR runs was supplied by Hamad et al . (2019a and 2019b ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteria, a group with no external cell wall and very small cell size, include a number of species of potential interest to humans, including pathogens of humans and livestock. One study demonstrated that starlings can carry species potentially detrimental to poultry [ 52 ], although another [ 53 ] failed to find evidence of infection in starlings. Little is known about their importance in the natural dynamics of these species in wild and captive animal populations.…”
Section: Resultsmentioning
confidence: 99%